Unique role of Mössbauer spectroscopy in assessing structural features of heterogeneous catalysts - Li, Xuning (2020)
Their wide availability in nature, low cost, high reactivity, and low toxicity make Fe-based catalysts versatile in various catalysis fields, including photocatalysis, Fenton-like reaction, electrocatalysis, Li-ion batteries (LIBs), Fischer–Tropsch synthesis (FTS), biomass conversion, N2O decomposition and etc. Mössbauer spectroscopy, a powerful technique that is able to give account of structural features for all iron species taking part in the catalysis process, is considered to be a crucial technique for determining catalyst phase, identifying active site, and investigating correlations between catalytic behavior and the coordination structure of catalysts, which are highly desirable for clarifying the catalytic mechanisms. Each kind of Fe-based materials could be functionalized in the most suitable catalysis field, wherever Mössbauer technique may play a unique role. For instance, Fe-N-C based materials are extensively investigated as electrocatalysts for oxygen reduction reaction and Mössbauer spectroscopy application in this field has been utilized to identify the chemical nature of the active site on the Fe-N-C catalyst. Iron carbides are considered as the most active phase for FTS and Mössbauer technique is widely applied in determining the chemical phase of catalysts. Fe-based silicates, phosphates or polyanionic compounds are recognized as promising cathode materials for LIBs, for which Mössbauer technique has been mainly applied for tracking of the oxidation state and coordination environment change of Fe between charged and discharged states of the batteries. Similar phenomena can also be found in other catalysis fields. To give a clear understanding of which field is most suitable for a certain Fe-based catalyst and the best role of the Mössbauer technique in a certain catalysis field associated with the investigation of the mechanism, in this review, the recent advances of applying Mössbauer technique in catalysis are thoroughly summarized, including results from environmental catalysis and energy catalysis. Remarkable cases of study are highlighted and brief insight into applying Mössbauer technique for various Fe-based materials in their special catalysis field is presented. Finally, the trends for future potential applications of Mössbauer technique are discussed.